Chick Lit in Translation: From Dietland to Sıfır Beden Cehennemi - Hilal Erkazancı Durmuş (İstanbul Üniversitesi Çeviribilim Dergisi)
This study seeks to analyze Sıfır Beden Cehennemi [Size Zero Hell], the Turkish translation of Dietland, a chick lit novel authored by Sarai Walker in 2015, to deconstruct some traditional chick lit discourses and the commodification of the female body. The aim of the study is threefold: (i) to illustrate how the discourse strategies of otherness that subvert the marginalization of the fat female body are immersed in Dietland, (ii) to examine how these strategies are reflected in the Turkish translation, and (iii) to analyze the examples from the perspective of feminist translation. The study first focuses on the chick lit genre within the context of feminism and sheds light on the genre’s linguistic and textual features. It further carries out a comparative analysis on the source and target texts. Ultimately, the study concludes that the source text’s deconstructive discourse has been recreated in the Turkish translation through discursive othering strategies and paratextual materials, as well as through the feminist translation strategy of supplementing.